Cooking and eating together in London: Food sharing initiatives as collective spaces of encounter - Marovelli, Brigida (My University, 2019)
Commensality, the act of eating together, is an important human ritual that benefits beyond the biological need for food and it is well established amongst food studies scholars. At the same time, novel forms of social eating are emerging in urban contexts, especially mediated by new technologies. Yet, ICT-mediated urban food sharing and the moments of commensality they generate have received limited attention to date. In response, this paper draws on ethnographic fieldwork with three urban food sharing initiatives in London - a city which exhibits an active and dynamic urban food sharing ecosystem, to explore the experiences of commensality that are produced. By employing qualitative methods of enquiry, I illustrate how these initiatives go beyond the food offered by engaging with the material and affective elements of cooking and eating together and how they attempt to nurture collective spaces of encounter. Social isolation and loneliness emerge within this research as central drivers for participating in food sharing initiatives. The paper concludes that these collective spaces and the affective qualities that they generate are particularly vital in urban contexts in times of austerity, as these initiatives have capacity to embrace social differences and to facilitate the circulation of ideas and practices of care and hospitality. They operate as provisional bridging mechanisms between people, communities, projects and services, providing the connective tissue in ways which are hard to measure through simple quantitative measures and, as a result, are rarely articulated.
Keywords: Commensality; Conviviality; Collective spaces; Urban studies; Food sharing; London